Perspective in image-guided surgery: proceedings of the Scientific Workshop on Medical Robotics, Navigation, and Visualization : RheinAhrCampus Remagen, Germany, 11-12 March - Buzug, Thorsten M.; Lüth, Tim C. (World Scientific Pub. Co, 2004)
The application of computer-aided planning, navigation and robotics in surgery provides significant advantages due to today's sophisticated techniques of patient-data visualization in combination with the flexibility and precision of novel robots. Robotic surgery is set to revolutionize surgical procedures. Augmented with 3D image-guidance technology these tools give finer control over sensitive movements in diseased areas and therefore allow more surgical procedures to be performed using minimally invasive techniques. This book provides an overview of new image-guided procedures in all areas of medical application
Includes bibliographical references
Keywords: Electronic books; Konferenzschrift